THE IMPLEMENTATION of PICTURE PUZZLE to TEACH WRITING DESCRIPTIVE TEXT to THE SEVENTH GRADERS (RETAIN, 2014)
THE IMPLEMENTATION of PICTURE PUZZLE to TEACH WRITING DESCRIPTIVE TEXT to THE SEVENTH GRADERS Christyanti Juwita English Department, Language and Arts Faculty, State University of Surabaya Tyannasetya@gmail.com Fahri English Department, Language and Arts Faculty, State University of Surabaya Fahriali267@yahoo.co.id Abstract This study focuses on the effectiveness of using picture puzzle to teach writing descriptive text. Because this kind of picture generally presents a visual representation of an object,scene,person that can help the students to write descriptive paragraph easily.In this study, the writer used descriptive qualitative research. The writer would describe and analyze the existing phenomena during study. The subject of this study is students of 7-A SMP Muhammadiyah 5 Bungah, Gresik. Moreover,there were three kinds of instruments used in this study, they were observation checklist, questionnaire and students’ writing. The research was conducted in two meeting. In every meeting the teacher gave an assignment.From the result of the study, the use of picture puzzle help the students in writing descriptive text and makes the students easily to identify the generic structure and language feature of descriptive text. It can be proved from the students writing progress in the term of each component. It could be conclude that the use of picture puzzle in composing descriptive writing could stimulate the students’ idea to write a good text. Keywords: Teaching writing, descriptive text, picture puzzle, seventh graders Abstrak Penelitian ini fokus pada efektivitas penggunaan puzzle dalam pengajaran menulis teks deskriptif . Karena jenis gambar umumnya menyajikan representasi visual obyek , adegan , orang yang dapat membantu siswa untuk menulis paragraf deskriptif dengan mudah .Dalam penelitian ini , penulis menggunakan penelitian deskriptif kualitatif . Penulis akan mendeskripsikan dan menganalisis fenomena yang ada selama penelitian . Subjek penelitian ini adalah siswa dari 7 - A SMP Muhammadiyah 5 Bungah , Gresik . Selain itu, ada tiga jenis instrumen yang digunakan dalam penelitian ini , mereka cheklist selama observasi, angket dan hasil menulis siswa . Penelitian ini dilakukan dalam dua pertemuan . Dalam setiap pertemuan guru memberikan tugas kapada siswa.Dari hasil penelitian , penggunaan puzzle bergambar membantu siswa dalam menulis teks deskriptif dan membuat siswa mudah untuk mengidentifikasi struktur organisasi dan fitur bahasa teks deskriptif . Hal ini dapat dibuktikan dari siswa memiliki kemajuan menulis dalam jangka waktu masing-masing komponen . Hal ini dapat disimpulkan bahwa penggunaan puzzle bergambar dalam menyusun penulisan deskriptif bisa merangsang ide siswa untuk menulis teks yang baik. Kata kunci: Pengajaran menulis , teks deskriptif , puzzle , siswa kelas tujuh . Introduction English is essential to be taught to younger people, for this case; the elementary students up to the senior high school students. In developing the student ability in mastering English, it cannot be sparated from writing mastery bucause it can be as meansurement for students’ English understanding. The need of learning English becomes very important. Indeed, English is the international language that the students of all around the world need to be learned most. Beside, English nowdays has not only become international language which is used in international communication, but also the language of science and technology (Jazadi,2004) The learners should be able to use English just like their own native language, not as knowledge anymore. Furthermore, in order to be a good communicator in English, the learner also have to have good discourse or communication competent. Discourse/communication competent is the competent to comprehend/or produce spoken text/or written text that are formed in the four language skills, they are listening,speaking,reading, and writing skill (Depdiknas,2004:8) Writing is important in the process of language learning. Writing ability develops after the students receive the listening and reading comprehension. It is one way of communication. As stated by Petty and Jansen (1980:361), writing is an important medium for self expression for communication snd the discovery meaning is used to give signal or information to other. Some people also believe that writing skill is a natural talent. Other words it can be said that someone being able to write well because they are destined to be a good writer. As far as researcher know,those all mindset are not 100% true. Young and Savage (1982:135) stated that writing skill could not come automatically. It requires some experiences, attention, and a lot of regular training. Probably, writing is actually difficult, but isnot imposible to someone to master it. Being able to write well is not only depending on the talent. Just remember, that essentially everybody can write, they just do not accustomed to or do not like to write. Just notice, that some skill being able to write well by learning and experiencing the strategies and the principles of writing; and than they practies then continously. To be able to write well are influenced by many aspect,one of them are knowledge, and another experiences. More and more knowledge and the experiences that somebody gahtered will make their writing product more and more than good. Meanwhile,writing is more emphasis in process. Writing process are, in which in order to have a product of writing someoneare should begin it with braistorming, prewriting, drafting, revising; till she/he get the final product of writing. In Lestari paper said that an individual’s success in college is to a great extent determined by his ability to write (2008:1) It means write not only as the subject when the student was obeyed to get high mark but also how they can practise it into reality. In fact many junior high school students, are still have difficulty in write a compositions; even though it is just for simple composition. It also support by the reseacher experiences when she was at the junior high school. There are so many students that are not able to construct smoothly even it is only a short composition. For example, for writing a simple descriptive composition, the students consume a plenty of time to finish it. They look like confuse and do not know with the things that they will write. The reseacher believe that the main problem is rooted in creating idea. Just think if the students can create and organize their ideas smoothly, the reseacher believe that they will able to write faster, better and easier. In teaching learning process, it is not easy to teach writing, especially to the non-native learners. The curriculum asks the students to perform a written text, but they tend to be asked to answer questions in their text book or worksheet rather than organize a text. In addition, in teaching children, teachers are supposed to be more enthusiastic to retain the learners’ attention and arouse their interest. The English teacher plays a very important rule to encourage likeness and curiosty in learning English and develop the students’ acuisition in English. Hailliwell (1992:18) furter said that students love discovering things, they respond well to being asked to use their imagination, they may well be involved in puzzel like activities; in making things, drawing things, games, physical movement or in song. Based on those statement, the researcher chooses Picture puzzle as media to teach and increase the students’writing in English. In teaching writing decsriptive, students have difficulty when they creating and stimulating idea. Because of that problem, teaching writing to the students in the seventh graders is not easy job for the teacher. The english language is very different with mother tongue; it makes them have difficulties in speaking , listening, and writing English. Moreover the teacher needs a good media for teaching writing descriptive to seventh graders student. Then, a solution to solve the problem is using picture as a media in teaching writing descriptive. According to Loukotkova (2009) there are some activities using picture such as picture card games, picture puzzel, flashcard, photograph and magazine pictures , wall charts, posters, blacboard drawing, word picture, picture coloring, etc. Picture puzzel is on of media that the student can create and construct their knowledge thrugh playing with piece of picture. It can be said if picture puzzle is an effective media for answer the problem. The teacher can choose the suitable media, based on the purpose, material and the student condition. To teach writing descriptive text easily, the teacher have to use various media. In this case I uses picture puzzle as a media in teaching writing descriptive text at seventh graders students. In addition, picture puzzle is communicative, interesting and effective way in teaching writing descriptive text. Puzzle is representation or visual likeness of single person objects. Picture puzzle is one way to motivate the students. In picture puzzles, the teacher can manage the class attention, so the teacher gives instructions to the students to arrange the picture puzzle or help the student to improve their writing while they doing their activities easily. It makes the teaching learning process more enjoyable and the lesson more interesting. Thus ,implementation of picture puzzle as a media of teaching writing descriptive text to seventh graders can help the students to get writing mastery after the implementation of picture puzzle in teaching learning process. Methods This study would be used descriptive qualitative as the research design. The process was done within descriptive research which invloved description and analysis without any manipulating the teaching learning activities. As state in Freeman and Longman (1991:11) that in qualitative methodology; the researcher does not set out to test hypotheses, but only observes when present during the observation As the researcher knows that qualitative research had a purpose of describing and analyzing phenomenom, event, social activity, attitude, believe, perception, or someone’s opinion and individual or group,this directed to explain or conclude. Qualitative research had two main purposes, the first was to describe and to explore,and the second was to describe and to explain (Sukamadinata,2005:60) In this study, the researcher used descriptive qualitative research to get information of “the implementation of picture puzzle to teach writing descriptive text for the seventh graders” . The researcher observed the use of picture puzzle in teaching writing descriptive text in the classroom and the student’s responses to the material used by the teacher. The subject of the study are the students of seventh grade of junior high school students. These student selected with consideration that at their age they are still consider as young learners, who get English lesson at their first level in the junior high school. Another consideration whay the observer chosen the VII- A class of Smp Muhammadiyah 5 Bungah were they had to study about the descriptive text (based on competence and curriculum). And it was expected that they were able to produce descriptive text. The data obtained to answer research question study. The data was about the implementation of picture puzzle in teaching writing process. The data themselves expected to get the information on the whole aspect of the implementation of picture puzzle in writing descriptive text, the students responses toward the implementation of picture puzzle and the students writing after the implementation of picture puzzle. The first data came from observation checklist. The second data come from the result of questionnaire. The third data were result of the students descriptive writing or the students composition. The data used to explain the influence of implementation of picture puzzle in teaching writing descriptive text at the seventh graders. In this study, the researcher could be considered as the key instrument because the researcher conducted a direct observation and analyzed the date. It was state by neuman (1991:355) that the researcher was able to be alert and sensitive to what happened in the observation checklist and questionnaire. After collecting the data, an analysis toward the data was needed. Firstly, the data from observation checklist was analyzed descriptively based on phenomena occurred when the teaching-learning process happening. Secondly, the data from questionnaire. The questionaire would be answered by the students’. It was analyzed descriptively the students’ interest of picture puzzle. The third, the researcher also analyzed and describe the students’ writing in order to know how their descriptive writing after they are thaught by using picture puzzle. In this case , the researcher analyzed the students’ writing using the components of descriptive text (generic structure and linguistic features). Generally, the students writing are analyzed based on five aspect, those are : content, organization, vocabulary, language use, and mechanics. The scoring are taking from Teaching ESL Composition by Jacobs Holly(1983:140). The result of the students writing task were gave the researcher information about the students ability in writing descriptive text using picture puzzle as a media. After analyzing the data, the researcher would have an organized information about how the media Picture puzzle happened in the real EFL classroom (how the teacher implemented it, how the students responded to it, and how the students writing compositions are,etc). RESULT How is the students’ writing ability of SMP Muhammadiyah 5 in writing descriptive text after they being taugh by picture puzzle. The result of students' writing composition was used to know that the implementation of picture puzzle helped the students in writing descriptive text. The researcher collected the students' writing composition from the first implementation and second implementation. In this case, the researcher suggested grading the students' writing by using ESL composition profile. There were five aspects of ESL composition profile; content, organization, vocabulary, language use, and mechanic: Each aspect was categorized into four criteria. Those criteria were excellent to very good, good to average, fair to poor, and very poor. Content was an important aspect in composition since it conveyed the main ideas of the writer. The criteria of evaluating the aspect of content are how knowledgeable the text, substantive, thorough development of the thesis, and relevant to the topic/genre are. Here, the researcher discussed and gave examples of student's composition that improved in term of content. Here are example of student writing composition that the category was very good. Figure 4.1 Students writing composition This was kind of students writing composition. Their writings can be categorized as good writing. The content of their writing was clear and understandable enough. Beside that and it had focus on specific participant and relevant to the topic of descriptive text. They could describe it in detail. They did it with a good discussion, although, sometimes they were not in one thought. But they learnt to accept different ideas and then incorporated them into a good paragraph. The organization of students' composition was scored based on how well, logic, fluent, and cohesive the students organized the composition. The organization dealed with the generic structure. In writing descriptive text, the composition produced should consist of thesis statement, arguments, and recommendation. Here, the researcher discussed and gave examples of student's composition that improved in term of organization. The criteria of scoring were excellent to very good, good to average, fair to poor, and very poor. These example below would present the students’ compositions. Figure 4.2 Students writing composition It could be seen that the students could write with the fluent expressions which clearly stated the main ideas they had. It also could be seed that the students wrote in a logical squencing with means they already develop a complete part of descriptive that identification and description. Then they got very good in their compositions. The aspect describe the students knowledge in vocabulary matery. To be specific, it would be presented how far students have mastered new words in their writing. Thus, it was classified four criteria, they are excellent to very good (effective word choice and usage), good (adequate, range, occasionally errors of word/idiom from and choice), fair to poor (limited range, frequent errors, of word/idiom), and poor (confusing, meaning and little knowledge of English vocabulary). Figure 4.3 Students writing composition The examples above showed that the pharagraph consisted of many important ideas, had a good choice of word and used it effectively. Therefore, the students got very good. The aspect of language use dealed with tense, number, word order or function, articles, pronouns, and preposition. Since the composition analyzed was descriptive text, the evaluation of language use included the use of simple present tense, subjective opinions, abstract nouns, adverbs, modals, connective, emotive words, compound and complex compound. Here, the researcher discussed and gave examples of student's composition that improved in term of language use. The criteria of scoring were excellent to very good, good to average, fair to poor, and very poor. Figure 4.4 Students writing composition From the examples above it could be seen that the students were able to use the language aspect in the right order. There were few mistakes found in the students’ compositions. In other word, the students did not find any difficulties in this aspect. Most of tenses, word. Articles, pronouns, and preposition were incorrected order. In order to make the composition readable, the students should pay attention to the mechanics of writing. It dealed with the spelling, punctuation, and capitalization. Here, the researcher discussed and gave examples of student's composition that improved in term of language use. The criteria of scoring were excellent to very good, good to average, fair to poor, and very poor. Figure 4.5 Students writing composition The example above presented very good writing for mechanics. It showed that there were few errors of spelling, punctuation and capitalization. The observations in the implementation of picture puzzle to teach writing descriptive text were done in two times. From the first observation in first implementation, the researcher saw that there were some students got problems in producing sentences. This was caused by their little experiences of writing. Students should often practice writing in order to make them used to create sentences become paragraph. According to Reid (1993: 98), teacher should allow students sample opportunities to write, not just talk about how to write. The teacher should allow the students to practice writing as much as possible. It was used to train them in producing composition. Practically, students were rarely given enough opportunity to practice making sentences in classroom. The students' vocabulary which was limited and the low mastery of grammar led them feel jittery in making composition. However, the researcher concluded that Picture puzzle could increase student's descriptive writing ability. She stated like that because he saw that students were very enthusiastic in writing when they were asked to make a composition based on picture puzzle that they got. The students got inspiration and opinion about the picture. Therefore, they could enjoy writing descriptive text easily by seeing the picture to stimulate ideas in writing descriptive text. Conclusions Picture puzzle can be used to teach writing descriptive text. Teaching descriptive text using picture puzzle is success. It could be seen from students who are very enthusiast in teaching learning process by using picture puzzle. The data from the observation result showed that students’ skills have increased. It was approved from the analysis of students’ composition done by researcher that there was better done by the students. Because teaching writing by using picture puzzle makes students easly to absorb their new knowledge and they can write their idea based on the picture in puzzle then produce good descriptive text. Picture puzzle can help the to look for the ideas in writing the descriptive text. So, they can use new vocabularies creatively. Picture puzzle could help the students in mastery the material related to the descriptive text genre. Previously they said that they do not like learning English and get difficulty to write, especially in writing descriptive text. By using picture puzzle they become interested and more enthusiastic in writing descriptive text. Beside that the teacher also gives them a good motivation while implementing picture puzzle. Students also said that picture puzzle make them easier to get the idea to write descriptive text. References Byrne, Donn.1984.Teaching Writing Skills.Hongkong:Longman Group Ltd Carter, Carol et al.2002. Key to Effective Learning. Third Edition. Upper Saddle River, New York: Pretice Hall Depdiknas. 2004. Kurikulum 2004 Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah pertama dan Madrasa Tsanawiyah. Jakarta:Pusat Kurikulum, Balitbang Depdiknas. Finocchiaro, Mary. 1975. Visual Aids in Teaching English As A Second Language. Washington D.C: English Teaching Forum Harmer, Jeremy.2001. The Practice of English Language Teaching. Edinburgh Gate Harlow Essex: Pearson Education Limited.